Torsional repair of damaged single-box multi-cell composite box-girder with corrugated steel webs using CFRP. Part Ⅰ: Experimental investigation. (15th September 2022) - Zhu, Yingbo; Shen, Kongjian; Wan, Shui; Brigham, John C.; Fascetti, Alessandro; Zhou, Peng
Highlights: A viable externally-bonded CFRP technique for repairing the torsional damaged SBMC-CBGCSWs is proposed. Torsional behavior of CFRP-repaired specimens is compared with the undamaged case. Crack torques of CFRP-repaired specimens are significantly restored due to the confinement effect granted by the CFRP. Yielding and ultimate torques of CFRP-repaired specimens are restored to 86–97% of their original values. A simplified method is proposed to predict the torsional capacity of CFRP-repaired specimens, which is shown to yield accurate predictions. Abstract: In the last two decades, Composite Box-Girders with Corrugated Steel Webs (CBGCSWs) have been extensively used in construction, but more research is still needed to fully characterize their mechanical behavior such as their torsional stiffness exhibiting a sharp decrease compared with concrete structures, due to the employment of the thin corrugated steel webs. Further, wide Single-Box Multi-Cell CBGCSWs (SBMC-CBGCSWs) under heavy eccentric load are more likely to damage suddenly than traditional concrete structures. Thus, the repair and rehabilitation of SBMC-CBGCSWs damaged by torsional effect have become increasingly necessary. In this paper, an externally-bonded Carbon Fiber-Reinforced Polymers (CFRP) retrofitting technique is presented to repair the damage caused by torsion in SBMC-CBGCSWs, and a test on CFRP-repaired SBMC-CBGCSWs is performed to quantify their torsional response in terms of failure modes, torque-twist curves and strains in the concrete slabs, CFRP and corrugated steel webs. The comparison between CFRP-repaired specimens and the control specimen indicates that CFRP can significantly improve the cracking, yielding and ultimate torques of damaged specimens, as well as the initial torsional rigidity. The experimental results also show that the torsional capacity of CFRP-repaired SBMC-CBGCSWs can be restored to 86–92% of the original specimens, which demonstrates that the externally-bonded CFRP technique is a viable and effective method to repair damaged SBMC-CBGCSWs. Lastly, a simplified method is developed to calculate the torsional capacity of the repaired SBMC-CBGCSWs using CFRP, and the quantification of its effectiveness is presented.